Perilaku Konsumen terhadap Keputusan Pembelian Sayuran secara Online pada Masa Pandemi Covid-19 - Anggraeni, Elisa Lintang; Maria, Maria (Seminar Nasional Lahan Suboptimal, 2021)
Anggraeni EL, Maria M. 2021. Consumer behavior towards online vegetable purchasing decisions during the Covid-19 pandemic. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 355-364. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The spread of the Corona Virus in Indonesia and the imposition of a lockdown or restrictions on movement are the catalysts for accelerating the adoption of wider use of technology, including online shopping or e-commerce. Vegetable producers must be able to adjust the direction of consumer trends during the Covid-19 pandemic so that the market remains created. The objectives of the study were (1) to determine the characteristics of consumers who buy vegetables online and their responses to the differences in purchasing systems (online and traditional) and (2) to determine the factors that influence consumer behavior towards online vegetable purchasing decisions. The approach used is descriptive quantitative with purposive sampling method. The research was conducted at Bale Hydroponics Salatiga and Jinawi Fresh Farm. Respondents consisted of 50 people. Data analysis used validity test, reliability test, classical assumption test, t test, and multiple linear regression test. The results showed that there are characteristics of consumers who buy vegetables online, namely age 21-27 years, female gender, most occupations are self-employed, monthly income is more than Rp. 2,000,000, online media used by Instagram and WhatsApp, frequency of making purchases 2 times a month. There are differences in consumer considerations in buying vegetables online and traditional. The consideration of consumers in the online purchasing system is time efficiency. While traditional purchases are competitive prices. The factors that influence online purchasing decisions are price (X2) and lifestyle (X4). While trust (X1) and quality (X3) have no effect on online purchasing decisions.